Pengaruh Beban Kerja dan Benefit Kerja terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Mediasi pada Pt. Wom Finance Tbk Regional Jabodebek - Asep Hidayatuloh; Adrie Frans Assa (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of workload and work benefits on employee performance, with work motivation serving as a mediating variable at PT. WOM Finance Tbk Regional Jabodebek. This study employed a quantitative approach, with data collected through questionnaires distributed to 162 employees selected using a saturated sampling technique. Data analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 4 software to examine the relationships among variables. The results indicate that workload has a significant effect on employee performance but does not significantly affect work motivation. Meanwhile, work benefits have a significant effect on work motivation but do not directly and significantly affect employee performance. Work motivation was found to have a significant effect on employee performance. In addition, work motivation was unable to mediate the effect of workload on employee performance but was able to mediate the effect of work benefits on employee performance. These findings suggest that improving work benefits and work motivation are important factors in supporting more optimal and sustainable improvements in employee performance at PT. WOM Finance Tbk Regional Jabodebek.